A review of expression profiling of circulating microRNAs in men with prostate cancer. (22nd May 2012) - Kelly, Brian D.; Miller, Nicola; Healy, Nuala A.; Walsh, Kilian; Kerin, Michael J.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? MicroRNAs are small, single‐stranded RNA molecules that are stable in the circulation. These molecules have been identified as potential circulating biomarkers for several malignancies. In this review we provide a comprehensive overview of the publications that have identified dysregulated microRNAs in the circulation of men with prostate cancer. MicroRNAs (miRNAs) are small non‐coding RNAs that are involved in gene regulation and expression. These molecules have been implicated in the pathogenesis of several malignancies. MiRNAs have the potential to be both a tissue‐ and blood‐based biomarker for cancer diagnosis, classification, prognosis and response to treatment. The levels of dysregulated miRNAs in the circulation of individuals make miRNAs an ideal biomarker for the detection of prostate cancer. The present study provides a comprehensive review of the expression profiling of miRNAs in the circulation of men with prostate cancer. Further research is necessary to identify if circulating miRNAs have the potential to be a biomarker for prostate cancer in clinical practice.